Designing the Learning Plan A Review of Research and Theory Related to College Curricula - Stark, Joan S.; National Center for Research to Improve Postsecondary Teaching and Learning, Ann Arbor, MI. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
A summary of major writings on college and pre-college curriculum literature are presented in this report, which is an early step in establishing a framework for the research program of the NCRIPTAL (National Center for Research in Postsecondary Teaching and Learning) Program on Curricular Integration and Student Goals. Section 1 on the literature of college curricula includes: historical and background reports (e.g., Carnegie Council on Policy studies); prescriptive views of quality, related to recommendations of national reports; strategy views, related to the educational process (e.g., national report recommendations, disciplinary approach, and discussions of student development); studies of curricular change (e.g., those at Alverno College, and liberal arts outcomes research). Definitions of curriculum are offered in the second section, which focuses on pre-college literature, as well as discussions in the literature of: the nature of curriculum development or planning; theoretical assumptions and approaches to curriculum planning and curriculum; cognitive psychology and curriculum development; and the teacher as curriculum planner. The final section proposes six assumptions for use in models of curriculum research, identifying such variables as student involvement, the organization of a discipline, and student outcomes. Fourteen pages of references are included. (LB)
Availability: NCRIPTAL, Suite 2400 School of Education Building, The University of Michigan, Ann Arbor, MI 48109-2748 (Technical Report No. 86-C-001.0, $10.00).
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: OERI-86-0010.
ERIC Note: From the NCRIPTAL Program on Curricular Integration and Student Goals.
Microfiche.
Keywords: College Curriculum; College Instruction; Curriculum Development; Definitions; Educational Research; Higher Education; Instructional Improvement; Planning; Research Design; Research Needs; Secondary School Curriculum; Alverno College WI -- College Outcomes Assessment; Information Analyses